SMEs and Innovation: Lessons from Cooperative Relationships between SMEs and Large Firms in Ireland, Japan and Other Asian Countries - Tomoko Oikawa (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
This paper discusses: (1) there exist a variety of small and medium enterprises (SMEs) in terms of nature, (2) SMEs are classified depending on activity in relation to innovation, (3) kanagatamaking enterprise in Japan is taken as an example of relationships with large enterprise, in comparison with tool making enterprises in Ireland, in terms of cooperation and innovation, (4) the community based performance of SMEs is shown in Japan, Thailand, and Indonesia in terms of solidarity, cooperation, and innovation. It would be claimed that innovation in SMEs could be distinctive from the case of large enterprises (LEs), and it is basic for SMEs to cooperate each other to be innovative. The paper argues: (1) there is a difference between Ireland and Asian countries in terms of cooperation among SMEs; the case studies show there exist few cooperation between SMEs or with principle firms in Ireland, (2) community-based innovative activity is picking up in the case of Japan and, apart from scale and scope, Thailand and Indonesia have witnessed the rise of community-based economic performance with innovation. While the nature of innovation between Japan and other South Asian countries is distinctive in terms of a variety of degree, and SMEs is overwhelmingly micro-sized in Thailand and Indonesia, it may be considered that there is a common feature in these countries. (3) It could be that their cultural core values are essentially community derived, but they are also the outcome of a bottoms-up approach to community actualities to the top-down state policy, which is based on the recognition of community power. This can be observed in Japan, Thailand and Indonesia. The paper claims the importance of cooperation for innovation both internally and externally. Cooperative activities are based on the cultural values of social structure, which can be observed in Japan as keiretsu relationships, ‘community culture (watthanatham chumchon)’ in Thailand, and ‘mutual spontaneous assistance (gotong royong)’ in Indonesia. However, the case studies of Irish toolmaking industry have possibly shown that principles such as keiretsu values can be learnt, even if partly so. Key words: SMEs, innovation, cooperative relationships, Ireland, Japan and other Asian countries